2022
DOI: 10.3389/fmed.2022.938005
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of National Early Warning Score and Modified Early Warning Score on intensive care unit readmission and mortality: A prospective observational study

Abstract: BackgroundModified Early Warning Score (MEWS) and National Early Warning Score (NEWS) are widely used in predicting the mortality and intensive care unit (ICU) admission of critically ill patients. This study was conducted to evaluate and compare the prognostic value of NEWS and MEWS for predicting ICU readmission, mortality, and related outcomes in critically ill patients at the time of ICU discharge.MethodsThis multicenter, prospective, observational study was conducted over a year, from April 2019 to March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The MEWS were considerably higher (P 0.001) in the ICU readmission, time to readmission, mechanical ventilation after readmission, mechanical ventilation duration, and multiple organ failure. According to the study's findings, the MEWS performed better in predicting other outcomes than the NEWS score 12…”
Section: Resultsmentioning
confidence: 96%
“…The MEWS were considerably higher (P 0.001) in the ICU readmission, time to readmission, mechanical ventilation after readmission, mechanical ventilation duration, and multiple organ failure. According to the study's findings, the MEWS performed better in predicting other outcomes than the NEWS score 12…”
Section: Resultsmentioning
confidence: 96%
“…As MEWS includes cardiac and pulmonary parameters, such as HR, RR, and blood pressure, which sensitively reflect patients’ circulation and fluid status, MEWS is able to assist in the earlier detection of patients who are becoming unstable and guides important interventions. Studies have demonstrated the reliable performance of MEWS for risk stratification in sepsis, trauma, and critical patients with ICU readmission [ 31 , 32 , 33 ]. In elderly patients presenting to the ED, MEWS has also been proven to be an effective tool for predicting in-hospital mortality [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, predicting all-cause mortality and assessing risk have consistently been crucial outcomes for clinicians [4][5][6][7][8][9] . Various scores and indices based on simple linear relationship have been proposed and used to predict mortality; however, their accuracy is only moderate 4,8,10 .…”
Section: Introductionmentioning
confidence: 99%